Near‐surface hydraulic conductivity of northern hemisphere glaciers. Issue 7 (26th March 2018) - Stevens, Ian T.; Irvine‐Fynn, Tristram D.L.; Porter, Philip R.; Cook, Joseph M.; Edwards, Arwyn; Smart, Martin; Moorman, Brian J.; Hodson, Andy J.; Mitchell, Andrew C.
Abstract: The hydrology of near‐surface glacier ice remains a neglected aspect of glacier hydrology despite its role in modulating meltwater delivery to downstream environments. To elucidate the hydrological characteristics of this near‐surface glacial weathering crust, we describe the design and operation of a capacitance‐based piezometer that enables rapid, economical deployment across multiple sites and provides an accurate, high‐resolution record of near‐surface water‐level fluctuations. Piezometers were employed at 10 northern hemisphere glaciers, and through the application of standard bail–recharge techniques, we derive hydraulic conductivity ( K ) values from 0.003 to 3.519 m day −1, with a mean of 0.185 ± 0.019 m day −1 . These results are comparable to those obtained in other discrete studies of glacier near‐surface ice, and for firn, and indicate that the weathering crust represents a hydrologically inefficient aquifer. Hydraulic conductivity correlated positively with water table height but negatively with altitude and cumulative short‐wave radiation since the last synoptic period of either negative air temperatures or turbulent energy flux dominance. The large range of K observed suggests complex interactions between meteorological influences and differences arising from variability in ice structure and crystallography. Our data demonstrate a greater complexity of near‐surface ice hydrology than hitherto appreciated and support the notion that the weathering crust can regulate the supraglacial discharge response to melt production. The conductivities reported here, coupled with typical supraglacial channel spacing, suggest that meltwater can be retained within the weathering crust for at least several days. Not only does this have implications for the accuracy of predictive meltwater run‐off models, but we also argue for biogeochemical processes and transfers that are strongly conditioned by water residence time and the efficacy of the cascade of sediments, impurities, microbes, and nutrients to downstream ecosystems. Because continued atmospheric warming will incur rising snowline elevations and glacier thinning, the supraglacial hydrological system may assume greater importance in many mountainous regions, and consequently, detailing weathering crust hydraulics represents a research priority because the flow path it represents remains poorly constrained.